FACTORS AFFECTING INTERESTS AND CONSUMER ATTITUDES CONSUMES BACK DRINKING WATER REFILL IN YOGYAKARTA - One, Sumiyo; Nani Muryani, SU., Dra.; Lastari, SE., MM., Siwi (Management, 2010)
Drinking water is a basic requirement for every human being. The increasing public concern about health and the advancement of technologies that exist today has brought drinking water into a large bisis and delivery of mineral water brands such as Aqua, Aqauria, Ades, etc.. For years those brands dominate the mineral water market in Indonesia, but over time, the price of mineral water becomes more expensive. One consequence is that there began to emerge and business development of drinking water refill. By offering a much cheaper price, drinking water refill has an alternative choice for people who start declining purchasing power. Great feedback from the community is what makes drinking water business content more and more popular ualng by small entrepreneurs. With limited capital, this business is promising big profits in a short time, even more so in the city of Yogyakarta, where the population is dominated by students with minimal pocket money. On the other hand, employers also look at prospects for the future h currents. This can be seen through the attitude towards consumer interests, whether consumers have a tendency to continue to consume drinking water refill or not. One approach that can be used to understand consumer attitudes and their effects on consumer interests to behave is Palnned Theory of Behavior. This theory discusses the influence of attitude behavior, subjective norm and perceived control keprilakuan against consumer interests, in this study Theory ofPalnned Behavior applied to influence behavior attitude, subjective norm and perceived control keprilakuan against consumer interest to continue to consume drinking water refill. Past behavior variables are added to obtain better results. The results of this study with the t test and F test indicated that attitudes, subjective norms, behavioral control and past keprilakuan jointly significantly influence the formation of interest. Meanwhile, the measurement of interest through multiple regression analysis showed that the people of Yogyakarta has a more moderate interest to continue to consume drinking water refills, mean refill drinking water business does not have good prospects sukup future. Keywords: Drinking water refills, attitude, subjective norm, control keprilakuan, actors of the past, t test, F test, multiple regression.